Kānsammanā thāng Wichākān Wikrittakān thāng Sangkhom Thai, 20-22 Mēsāyon 2538, na h̨ōprachum yai, Sūn Watthanatham h̄æng Prathēt Thai (Samnakngān Khana Kammakān Watthanatham h̄æng Chāt, 1995)
Report of a seminar on social crises in Thailand organized to mark Thailand's cultural promotion year, 1994.